Impacts of ainuovirine-based and efavirenz-based antiretroviral therapies on the lipid profile of HIV/AIDS patients in southern China: a real-world study - Zhang, Quan; Chen, Zhong; Wang, Yating; Peng, Yongquan; Tan, Si; Li, Ying; Cao, Guiying; Bignotti, Antonia; Wu, Shangjie; Wang, Min (Frontiers in Medicine, 2024)
Background: The newly approved third generation oral anti-HIV-1 drug, ainuovirine (ANV) was used in combination with nucleoside reverse transcriptase inhibitors (NRTIs) in our study and its effects on lipid profile of antiretroviral-experienced HIV/AIDS patients are incomplete. Objectives: To examine antiretroviral agents' effects on lipid profile in patients with HIV-AIDS. Methods: We conducted a real-world prospective study involving treatment-naïve and -experienced adult participants living with HIV-1 infection provided with ANV or efavirenz (EFV)-based regimens. The primary endpoint was the proportion of participants with an HIV-1 RNA level of < 50 copies/mL at week 24 of treatment. Secondary endpoints included the change from baseline in CD4+ T cell count and lipid profile. Results: A total of 60 treatment-naïve and 47 treatment-experienced participants received ANV-based regimen, while 88 treatment-naïve and 47 treatment-experienced participants receiving EFV-based regimen were respectively matched to be as controls. At week 24 following treatment, the proportion of participants with an HIV-1 RNA level of < 50 copies/mL and the mean changes of CD4+ T cell counts from baseline were significantly higher in naïve-ANV group than those in naïve-EFV group (p < 0.01). Compared to EFV group, both naïve and experienced ANV group exhibited a favourable lipid profile, including constant changes in total cholesterol, triglycerides, and a significant decrease in LDL-cholesterol (p < 0.0001) and dramatic increase in HDL-cholesterol (p < 0.001).The efficacy of ANV was non-inferior to EFV when combined with two NRTIs. Patients receiving ANV-based regimens had decreased prevalence of dyslipidemia.